Contributions of ancient Arabs to modern translation studies "Al-jahiz and Hunayn ibn Ishaq as a model": إسهامات العرب القدامى في الدراسات الترجمية الحديثة "الجاحظ وحنين بن إسحاق أنموذجا" - KIRAT , Hichem; DIAF , Fatima Zahra (Maalim, 2024)
It has long been said that translation is a practice that predates theorizing, and the debate continues to this day whether there is a science of translation itself. Through this research paper we aim to prove that theorizing in the field of translation is not new as it is generally recognized but the practice of translation has led since ancient times to an attempt to restrict it and establish standards and foundations on which modern translation studies were based. The Arabs had an ample share in this matter, as Al-jahiz was one of the first to touch on the subject of translation and some of what related to its process. Hunayn ibn Ishaq, having translated many works into Arabic, also developed his strategies during the transfer process.